Enhancing Trauma Patient Experience Through Education and Engagement: Development of a Mobile Application. (March 2020) - Childs, Benjamin R.; Breslin, Mary A.; Andres, Brendan A.; Swetz, Anna; Hendrickson, Sarah B.; Moore, Timothy A.; Ho, Vanessa; Vallier, Heather A.
Abstract : Introduction: The purpose was to determine the utility of an open access mobile device application (App: http://bit.ly/traumaapp ) to improve patient education and engagement. Methods: A patient education app was developed with information regarding injury, treatment, and recovery for orthopaedic and other injuries. Data regarding usage, satisfaction, and desired improvements were gathered. Results: The app was downloaded 725 times, and the pages in the app were viewed 9, 043 times in 34 months. User sessions >2 minutes accounted for 34%. Participation was less in those older than 55 years (12% versus 68% P < 0.001). Sixteen percent of patients did not have a device to use the app. Most (55%) rated it as helpful or extremely helpful; 78% of users were likely to recommend it. Patients most frequently suggested more information on other injuries and simpler language. Discussion: There was strong interest in this simple, free patient education app. Despite an urban, trauma population, five of six patients had access to a device that could load the app. Nearly half of the patients downloaded an orthopaedic patient education app when offered. Those who did not use the app were more likely to be older than 55 years. This represents an innovative opportunity for education and engagement of our patients and their families.